OPTIMALISASI PENJUALAN ASET PROPERTI LELANG EKSEKUSI HAK TANGGUNGAN PADA BALAI LELANG MANDIRI PRASARANA DENPASAR PASCA PANDEMI COVID-19 - Julianti, Lis (Jurnal Aktual Justice, 2022)
One of the sales of objects that can be carried out through the auction mechanism is property assets that become collateral for mortgages which later in the auction will be referred to as mortgage execution auctions. During the Covid-19 pandemic, there was a decline in the sale of auction property assets. The purpose of this study is to find an effort to optimize the sale of property assets in the auction of mortgage executions as an effort to improve the investment climate in Indonesia and provide income for the country. This research is a normative juridical research using an approach based on secondary legal materials. This study uses the approaches: statute approach, and conceptual approach. The technique of tracing legal materials uses a document study technique (library research), and the analysis of the study uses qualitative analysis. The results of this study indicate that the efforts and strategies taken to optimize the sale of auction property assets are by educating the public and socializing through brochures in both mass media and social media as well as joint marketing with banks.